Benthic Carbon Mineralization in Hadal Trenches: Insights From In Situ Determination of Benthic Oxygen Consumption. Issue 6 (25th March 2018) - Luo, Min; Glud, Ronnie N.; Pan, Binbin; Wenzhöfer, Frank; Xu, Yunping; Lin, Gang; Chen, Duofu
Abstract: Hadal trenches have been proposed as depocenters of organic material and hot spots for organic matter mineralization. In this study, we for the first time quantified the total benthic O2 uptake in hadal trenches using in situ chamber incubations. Three trenches in the tropical Pacific were targeted and exhibited relatively high diagenetic activity given the great water depths, that is, the Mariana Trench (2.0 × 10 2  μmol O2  m −2  d −1, 10, 853 m), the Mussau Trench (2.7 ± 0.1 × 10 2  μmol O2  m −2  d −1, 7, 011 m), and the New Britain Trench (6.0 ± 0.1 × 10 2  μmol O2  m −2  d −1, 8, 225 m). Combined with the analyses of total organic carbon and δ 13 C of total organic carbon in the sediments and previously published in situ O2 microprofiles from hadal settings, we suggest that hadal benthic carbon mineralization partly is governed by the surface production and also is linked to the distance from land. Therefore, we highlight that terrestrial organic matter can be of importance in sustaining benthic communities in some hadal settings. Plain Language Summary: Hadal trenches that refer to seafloor areas covered by a water column with depths >6, 000 m have been proposed as depocenters of organic material and hot spots for organic matter mineralization. We applied in situ benthic chamber incubation techniques within three trenches in the tropical Pacific Ocean (the Mariana Trench, the Mussau Trench, and the New Britain Trench) and thereby reported the first benthic total O2 uptake rates measured in hadal settings. The benthic carbon mineralization rates generally show a positive correlation with the net primary production in respective provinces and the sedimentary total organic carbon (TOC) level. Analyses of TOC contents and δ 13 C of TOC indicated a downslope transport of sediment containing a large amount of terrestrial organic matter, possibly via mass‐wasting events to the axis of New Britain Trench off the New Britain Island. Therefore, we speculate that both surface production regimes and the distance from land are closely connected with the benthic carbon mineralization rate at the trench axes. The elevated organic carbon turnover rate may in part result from preferential concentration of relatively labile organic matter in the surface sediments of trench axes or efficient utilization of refractory terrestrial material under extreme pressure. Key Points: Total oxygen uptakes were measured for the first time in hadal trenches using in situ benthic chamber incubations Data compilation from hadal trenches suggests that rates of benthic carbon mineralization reflect the surface ocean productivity However, factors governing the diagenetic activity in hadal trenches apparently include supply of terrestrial organic material